Germination performance of grain sorghum hybrid seeds treated with bioregulator under water deficit - Werner, Flávia; Abati, Julia; Ferreira, André Sampaio; Aguiar e Silva, Marcelo Augusto de; Zucareli, Claudemir (Scientia Agraria Paranaensis, 2021)
Water stress can reduce seed germination speed and percentage, harming the development of seedlings. Thus, it is necessary to find alternatives that can mitigate these effects. Bioregulators have been intensively used in agricultural production and can provide increase in plant growth and development. Therefore, the aim of this work was to evaluate the germination performance of seeds of two grain sorghum hybrids under simulated water deficit treated with bioregulator. The experimental design was completely randomized in a 2 x 4 factorial scheme, with the following factors: two seed treatments (with and without bioregulator) and four osmotic potentials (0; -0.4; -0.8 and -1.2 MPa), with four replicates, separately for the following grain sorghum hybrids: 1G100 and 1G233. Germination, first germination count, shoot and root length and shoot and root dry matter were evaluated. Data obtained were submitted to analysis of variance and means were compared by the Tukey test at 5% probability and regression analysis. The reduction of the osmotic potential to the level of -1.2 MPa reduced the physiological quality of seeds; however, bioregulator application did not result in better seed quality under water stress. Bioregulator Stimulate® increased root length and shoot dry matter of seedlings of grain sorghum cultivar 1G233 in the absence of water deficit.